A Review on Applications of Particle Image Velocimetry - Hassan N.H.; Zawawi M.H.; Mustafa Al Bakri A.M.; Rozainy Z.M.R.; Kamaruddin M.A.; M Nasir W.N.Y.W.; Mazlan M.A.N.; Irfan A.R. (IOP Publishing Ltd, 2023)
Fluid dynamic field is frequently classified and designated into two which are hydrodynamics and aerodynamics. Particle Image Velocimetry (PIV) has been exerted to many flow problems in a broad range. PIV application to the measurement of velocity distributions in fluid flow is represented by the Stokes number. PIV can be executed to practically for any sort of flow if the fluid is transparent to allow suspended particles image. The purpose of this paper is to present some examples of application of PIV in general cases. In the midst of numerous applications of PIV, turbulent flows are the most comprehensively demanding because of their three-dimensionality, naturally large ranges of length and unsteadiness. Sudden flow field measurements of PIV method can be applied for the demotion of turbulence quantities and mean velocities. Published under licence by IOP Publishing Ltd.